Distinct genetic architectures and environmental factors associate with host response to the γ2-herpesvirus infections - Neneh Sallah (Nature Portfolio, 2020)
Disease prognosis after infection with Kaposi’s sarcoma-associated herpesvirus and Epstein-Barr Virus is highly variable. Here the authors carry out epidemiological and genetic analysis of a Ugandan cohort and suggest complex interactions may influence pathogenesis and transmission.